Systematics and reproductive biology of the genus Morus L. (Moraceae) - Nepal, Madhav P. (Kansas State University, 2008)
Morus L. (Moraceae) is a temperate and subtropical genus of ten to 15 species distributed in Asia, Africa, Europe, North, Central and South America. Despite its broad distribution and economic importance, it has received little attention from systematic botanists. Two species of this genus, the native M. rubra and the exotic M. alba, co-occur in eastern North America including the Flint Hills region of the Central Plains. In my dissertation research, I have conducted both species level and population level studies to obtain insights into the diversification of Morus. At the species level, my objectives were to re-evaluate the taxonomy and reconstruct the phylogeny of Morus. Based on herbarium and literature study as well as some field study, I recognize 13 species: eight species occurring in Asia, one in Africa and four in the New World. I used sequence data from the internal transcribed spacer (ITS) region of the nuclear ribosomal DNA and the trnL-trnF region of the chloroplast DNA to reconstruct the evolutionary history of Morus. The phylogenies were congruent and indicate a) a monophyletic core group of Morus with two well-supported geographical clades (one containing Asian taxa and one of New World taxa); and b) that Morus, as currently circumscribed, is non-monophyletic. At the population level, I studied sex expression pattern variation between the Morus native-exotic pair in the Flint Hills region, and assessed hybridization between these species at Konza Prairie Biological Station (KPBS). Both species are subdioecious, and Flint Hills populations exhibit significantly male-biased sex ratios, with sex expression being size independent. Approximately 10% of individuals of each species changed sex annually. In the population study at KPBS, I applied randomly amplified polymorphic DNA (RAPD) markers and microsatellites. The Morus species were moderately ([Theta]II = 0.079; RAPD data) to highly differentiated genetically (F[subscript]ST = 0.233; microsatellite data). Analysis of genetic structure suggested interspecific gene flow and indicated the presence of later generation hybrids. The presence of the exotic congener may affect the existence and genetic integrity of the native species. Overall, these studies contribute to our understanding of diversity in this interesting plant study system.
Keywords: Moraceae; Morus taxonomy; Phylogeny; Microsatellites; Subdioecy; Interspecific hybridization; Biology, Botany (0309)